Amygdala volume in schizophrenia: post-mortem study and review of magnetic resonance imaging findings. - Chance, SA; Esiri, M; Crow, T (2002)
BACKGROUND: Claims that schizophrenia is a disease of the limbic system have been strengthened by meta-analyses of magnetic resonance imaging (MRI) studies finding reduced hippocampus and amygdala volumes. Some post-mortem studies do not find these abnormalities. AIMS: To assess the volume of the amygdala in a series of brains post-mortem. METHOD: Amygdala volume was estimated using point-counting in both hemispheres of the brains of 10 male and 8 female patients with schizophrenia, and a comparison group of 9 males and 9 females. RESULTS: No significant reduction of amygdala volume was found. CONCLUSIONS: Significant volume reduction of the amygdala is not a consistent feature of schizophrenia; findings from early MRI studies using coarse delineation methods may introduce bias to subsequent meta-analyses.